High‐Contrast Magnetic Resonance Imaging and Efficient Delivery of an Albumin Nanotheranostic in Triple‐Negative Breast Cancer Xenografts. Issue 11 (16th September 2019) - Hafner, Susanne; Raabe, Marco; Wu, Yuzhou; Wang, Tao; Zuo, Zhi; Rasche, Volker; Syrovets, Tatiana; Weil, Tanja; Simmet, Thomas
Abstract: Triple‐negative breast cancer (TNBC) is a fast growing and strong metastasizing tumor, which presents almost no cellular receptors that can be addressed by targeted therapeutics. In addition, TNBC is often characterized by high tumor grading, fast growth rates, and early metastasis. Therefore, multifunctional drug carriers allowing efficient drug delivery and bioimaging to treat and track TNBC tissue in vivo would be highly desirable. A human serum albumin‐based polyethylene glycol copolymer (dcHSA‐Gd‐Dox) is synthesized combining multiple copies of the chemotherapeutic drug doxorubicin and gadolinium (III) (Gd(III))‐based magnetic resonance imaging (MRI) contrast agent. The biodegradable albumin‐based nanocarriers reveal high‐contrast tumor imaging and efficient drug delivery in a preclinical TNBC xenograft model, where the xenografts are grown on the chorioallantoic membrane of fertilized chick eggs. dcHSA‐Gd‐Dox is injected intravenously, and the distribution of the compound is monitored by MRI and inductively coupled optical plasma emission spectrometry. dcHSA‐Gd‐Dox is rapidly taken up into MDA‐MB‐231 cells and exhibits significant cytotoxic efficacy. dcHSA‐Gd‐Dox combines high tissue enrichment with low systemic toxicity and high‐contrast MRI rendering it an attractive nanotheranostic for TNBC. Abstract : An albumin‐based nanocarrier is designed enabling drug delivery of doxorubicin and high‐contrast magnetic resonance imaging at the same time in vivo. The nanocarrier shows enhanced signal‐to‐noise ratio in magnetic resonance imaging compared to commercial contrast agents and reduced tumor growth of MDA‐MB‐231 xenografts.